2019
DOI: 10.1007/s00520-019-04910-1
|View full text |Cite
|
Sign up to set email alerts
|

A mixed methods analysis of patients’ advance care planning values in outpatient oncology: Person-Centered Oncologic Care and Choices (P-COCC)

Abstract: Purpose-Person-Centered Oncologic Care and Choices (P-COCC) combines an advance care planning (ACP) value-focused patient interview with a care goal video decision aid. Our randomized study showed that P-COCC was acceptable but increased participant distress, compared with video-alone and usual care study arms. This mixed methods approach explores the ACP values in the P-COCC arm and their relationship to the distress phenomenon. Methods-Qualitative thematic analysis of the 46 audio-recorded P-COCC interview t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…The study results demonstrated increased distress (0.43) in the P‐COCC arm as compared to the video only arm (−0.04). The increased distress was noted again by Agarwal et al (2020) in their mixed method study that explored ACP values with a survey of the same study patients of the P‐COCC intervention arm ( n = 33). There was a reduction in anxiety and depression in the study population of Agarwal et al, 2020; Epstein et al, 2018.…”
Section: Resultsmentioning
confidence: 79%
See 4 more Smart Citations
“…The study results demonstrated increased distress (0.43) in the P‐COCC arm as compared to the video only arm (−0.04). The increased distress was noted again by Agarwal et al (2020) in their mixed method study that explored ACP values with a survey of the same study patients of the P‐COCC intervention arm ( n = 33). There was a reduction in anxiety and depression in the study population of Agarwal et al, 2020; Epstein et al, 2018.…”
Section: Resultsmentioning
confidence: 79%
“…Agarwal et al (2020) found a close relationship between distress associated with the CPR video and cancer patients' end‐of‐life preferences with less aggressive care and choosing no CPR at the end‐of‐life. The video provided most participants with sufficient information to make an informed decision to make EOL care decisions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations